The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/jam.15480
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilisimpact on plant growth, soil health and environment: Dr. Jekyll and Mr. Hyde

Abstract: The increased dependence of farmers on chemical fertilizers poses a risk to soil fertility and ecosystem stability. Plant growth‐promoting rhizobacteria (PGPR) are at the forefront of sustainable agriculture, providing multiple benefits for the enhancement of crop production and soil health. Bacillus subtilis is a common PGPR in soil that plays a key role in conferring biotic and abiotic stress tolerance to plants by induced systemic resistance (ISR), biofilm formation and lipopeptide production. As a part of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
69
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(71 citation statements)
references
References 159 publications
(150 reference statements)
1
69
0
1
Order By: Relevance
“…In an in-vitro seedling assay, this strain promoted plant growth by significantly increasing the vegetative growth parameters of wheat seedlings. The plant probiotic activity of this strain was comparable to that described in past studies, which showed that Bacillus subtilis is a rhizospheric bacteria with numerous favorable effects on crops and plants 2 , 29 , 30 .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In an in-vitro seedling assay, this strain promoted plant growth by significantly increasing the vegetative growth parameters of wheat seedlings. The plant probiotic activity of this strain was comparable to that described in past studies, which showed that Bacillus subtilis is a rhizospheric bacteria with numerous favorable effects on crops and plants 2 , 29 , 30 .…”
Section: Discussionsupporting
confidence: 82%
“…The majority of the researchers cited did not mention root length, stolon number, or transplanted plantlet survival rates, and there was no evidence of the use of plant probiotics in aeroponics such as Bacillus subtilis 46 49 . Bacillus subtilis CW-S performed well in aeroponic because it offered plants biotic and abiotic stress tolerance via induced systemic resistance (ISR), biofilm growth, and lipopeptide production 30 , 50 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of chemical agents can result in easily cause resistance to pathogens and environmental pollution and, thus, provides a challenging control method (Henkler & Luch, 2011). Beneficial plant micro‐organisms are recommended as biological control agents (BCAs) in agricultural production due to their safety and environmental friendliness (Li et al, 2014; Mahapatra et al, 2022). At present, the use of beneficial micro‐organisms to improve crop health, and alleviate and protect plants from stress has become a research priority (Sahoo et al, 2013; Yao et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Bacillus species produce various enzymes, antibiotics, vitamins, amino acids, organic acids and other substances, performing important functions in the natural environment as well as in the biotechnological industry [ 11 , 12 , 13 ]. Various Bacillus species have the potential to support plant growth, limit or fight plant pathogens and mitigate the effects of stress, e.g., salt stress, by colonizing the roots and regulating physiological and molecular processes in plants [ 11 , 12 , 13 , 14 , 15 , 16 ]. Bacillus sp.…”
Section: Introductionmentioning
confidence: 99%
“…Bacillus sp. colonize the soil environment and directly influence soil quality and the condition of plants, as they are involved in processes such as nutrient cycling, organic matter decomposition and symbiotic relations with plants [ 15 ]. Some Bacillus species benefit plants by supplying them with minerals via reduction of atmospheric nitrogen to forms available to plants.…”
Section: Introductionmentioning
confidence: 99%